Distributed circuits underlying anxiety - Adhikari, Avishek (Frontiers in Behavioral Neuroscience, 2014)
Anxiety is of paramount importance for animals, as it allows assessment of the environment while minimizing exposure to potential threats. Furthermore, anxiety disorders are highly prevalent. Consequently, the neural circuitry underlying anxiety has been a topic of great interest. In this mini-review we will discuss current views on anxiety circuits. We will focus on rodent anxiety paradigms, but we will also consider results from human neuroimaging and clinical studies. We briefly review studies demonstrating the central role that the amygdala and the bed nucleus of the stria terminals play in modulating anxiety and present evidence showing how the bed nucleus uses different output pathways to influence specific features of anxiolysis. Lastly, we propose that several brain regions, such as the medial prefrontal cortex and the ventral hippocampus, act in a coordinated fashion with the amygdala and the bed nucleus of the stria terminalis, forming a distributed network of interconnected structures that control anxiety both in rodents and humans.